SEBAB-SEBAB DAN UPAYA HUKUM DISKRIMINATIF DALAM KASUS KORUPSI TERHADAP PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 2573 K/Pid.Sus/2021 SERTA NOMOR 2451 K/ Pid.Sus/2021 - Maria Oktaviani Padur; Aksi Sinurat; Rudepel Petrus Leo (Petitum Law Journal, 2026)
In practice, judicial decisions in corruption cases often reflect discriminatory patterns in sentencing. This study aims to determine and analyze the causal factors or reasons for criminal discrimination in corruption cases Number 2573 K/Pid.Sus/2021 and Number 2451 K/Pid.Sus/2021 at the Supreme Court of the Republic of Indonesia, and to analyze the legal efforts that can be taken by the Public Prosecutor for criminal discrimination in corruption cases Number 2573 K/Pid.Sus/2021 and Number 2451 K/Pid.Sus/2021 at the Supreme Court of the Republic of Indonesia. This study seeks to explore the underlying causes and legal solutions for the presence of discriminatory sentencing in corruption cases. Employing an empirical juridical research approach, data were collected through interviews and literature reviews, then analyzed qualitatively. The findings indicate that the causes of discriminatory sentencing in corruption cases stem from both legal and judicial factors. Thomas More and Jonas Salean were charged together for the same act of transferring and distributing state land without legal basis. However, the difference in the legal fate of Thomas More, who was imprisoned for 8 years, and Jonas Salean was acquitted, raises an indication of criminal discrimination because the difference in treatment is not based on differences that are legally relevant.